The Least Developed Countries Report 2016 - United Nations Conference on Trade; Development (United Nations, 2016)
Graduation is the process through which least developed countries (LDCs) cease to be members of the LDC category, in recognition of their advances in development. In principle, it marks a shift from dependency to a greater degree of self-sufficiency and emergence from the development